Capturing life as it is truly lived? improving diary data in educational research - Arndt, H; Rose, HL (Taylor and Francis, 2022)
Diary methods have long been used as pedagogic tools in learning, and as part of reflective practice in teacher education, but less often as data collection instruments in educational research. This is in part due to implementation challenges emerging from the time and literacy demands they place on participants. To illustrate the use of diary methods in educational research, we juxtapose two diary studies to reflect on how to use diaries as data collection tools against a backdrop of researcher positionality. In the first example, the teacher-researcher embedded diaries in a curriculum to collect data from language learners in Japan. While learner engagement with the diaries was high, the prescriptive approach led students to tell ‘the teacher what they wanted to read’. In the second example, the researcher used the diaries to collect data on out-of-class learning among language students in Germany. Engagement with the diaries was initially low but improved substantially after daily reminders were sent via mobile phone. Nonetheless, results revealed a possible self-selection bias. Both examples highlight the value in making adaptations to diary methods as the research context necessitates, so that researchers can take into account issues that might distort or produce misleading data.